Greening and agroecological assessment of the agricultural sector of the Karabakh region - Mehdiyeva, Valida; Khalilov, Ilgar; Eminov, Farhad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
State of the problem. During the occupation by Armenia of the Karabakh economic district of the Republic of Azerbaijan, the military degradation of agricultural lands and their use in agriculture and animal husbandry without observing agroecological rules led to the deterioration of soil fertility and the reduction of the optimality of agrarian landscapes. Object learning. The article presents modern ideas for re-doing the agroecological assessment of the lands and solving the actual agroecological problems of their use in agriculture for greening the development of the agricultural area in the Karabakh economic region. In the economic region, the main approach is given to methodological issues of agro-ecological assessment of soil quality, greening of efficient use of agricultural land, agro-ecological analysis of anthropogenic dynamics of soils, regional integration of assessment of agro-ecological quality of soils. In the design of agroecosystems in the Karabakh economic region, the agroecological approach of the differentiation of the area according to the soil-climate factors, the evaluation of the soil taking into account the geomorphological and climatic factors is given. At the same time, the importance of cadastral assessment and accounting of the modern ecological condition of the region’s land resources, as well as the issues of their effective use and protection are explained. In the article, in order to ensure the development of the agrarian sector in the region, the importance of the complex agro-ecological re-evaluation of land resources, ways to eliminate the main indicators of land degradation and ecological requirements for the cultivation of plants, determination of territorial units characterized by variability of natural and climatic conditions, agro-production grouping of elementary areas of agro-landscapes and according to the agro-ecological assessment of the area, the ways of organizing the efficient use of land were investigated. Methodology. Generalization, historical, statistical, systematic analysis, and comparison methods were used to prepare the article. Research results. Environmental and economic stability may become more challenging in the future due to increasing anthropogenic pressure on agroecosystems in the economic region and poor infrastructure. Due to intensive land use, frequent erosion, river floods, and environmental pollution in the region can lead to a decline in the quality of agricultural land. Also, anthropogenic activities in the region can have a negative impact on the state and development of agroecosystems and the sustainable development of agriculture in the region, to optimize which it is considered necessary to improve and update the methods and technologies used in agriculture. The scientific novelty of the research. It is necessary to apply agroecological concepts and principles in the redesign, development, and management of sustainable agricultural systems in the economic region. The development of agroecosystems in the region should be ensured by alternative agricultural methodologies and approaches that combine the socio-economic and historical context of agriculture. The production of organic agricultural products, which do not harm human health and the natural environment, should be carried out, and the ecological condition of the soil should also be monitored regularly.